Injury epidemiology of Ultimate Frisbee in Hong Kong - Florence Ou-Suet Pang; Gene Chi-Wai Man; Samuel Ka-Kin Ling; Patrick Shu-Hang Yung (Elsevier, 2021)
Background: Ultimate Frisbee is a non-contact, self-refereed team sport that is rapidly gaining popularity in Hong Kong. As it is a physically demanding competition, it can result in substantial injury risk. However, the injury epidemiology data in Hong Kong remains lacking. The aim of this study is to identify and analyse the injury prevalence and risk factors for Ultimate Frisbee players in Hong Kong. Methods: Online self-reported surveys were collected from participants through the Hong Kong Flying Disc Federation for the 2019 season. Data was collected on injury type, location, nature, severity and onset. Injury incidence rates (IRs) were calculated as injuries per 1000 h of athlete-exposures (AEs). Incidence rate ratios were determined to compare IRs with 95% confidence intervals, which were used to calculate differences. In addition, analysis on IR will be made on comparing between training and tournament. Results: Response rate of 75.6% was achieved, of which 59 entries were included for analysis. We observed 54 injuries over 9412 AEs for a total IR of 5.74 per 1000 h of AEs. The injury prevalence is 62.7%, with both men and women having similar incidence (IRR = 1.161, 95% CI = 0.63, 2.14, p = 0.63). The most common injuries were in the lower limb (61.1%). Cutting was the most frequent injury mechanism (23.7%). The risk of injury during training is 3 times less compared to during tournament (IRR = 0.03, 95% CI = 0.18, 0.60, p < 0.01). Conclusion: Our preliminary findings provide evidence that majority of Ultimate injuries in Hong Kong players involved the lower extremity with injuries occurring more in tournaments than training. This study is an important first step to provide the groundwork for tailoring prevention strategies to minimize injuries in Ultimate Frisbee.